ANALISIS EFFECT SIZE PENGARUH BAHAN AJAR CETAK BERUPA MODUL PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Rissa Pramita; Asrizal Asrizal; Festiyet Festiyet (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2021)
The 21st century is marked as the century of openness or the century of globalization. In other words, human life in the 21st century undergoes fundamental changes that are different from the order of life in the previous century. The 2013 revised 2017 curriculum is one of the efforts made by the government to improve education in Indonesia. Where the 2013 revised 2017 curriculum integrates four things in learning, namely 1) strengthening character education, 2) literacy movement, 3) 4C skills, and 4) Higher Order Thinking Skill (HOTS). This study focuses on the 4C skills, namely critical thinking. In improving critical thinking skills, supporting learning resources are needed. One of them is printed teaching materials in the form of learning modules according to the characteristics of students. This study focuses on the effect of printed teaching materials in the form of learning modules on students' critical thinking skills. This study aims to determine how much influence printed teaching materials in the form of modules have on students' critical thinking abilities. The research method used is the article review method by reviewing 20 journal articles at the junior and senior high school level on science and physics material. From the data analysis that has been carried out, it can be concluded that printed teaching materials in the form of modules have a significant influence on students' critical thinking skills. This can be seen from the results of the analysis of the material at the education level, learning models and the results of the analysis of all journals based on learning modules on students' critical thinking skills